Democratizing and Dehegemonizing Literature*: Endeavours of Empowerment - Sivasubramaniam, Sivakumar (Armenian Folia Anglistika, 2009)
Currently, hegamonization and democratization introduced through literature results in indifference towards literature among students which, in its turn, gradually leads to decrease of interest towards literature.The article offers to create such programs which will develop text-oriented approach towards literature, i.e. teachers should be free to select the material which will boost the language skills of the students and will enrich their imagination.Only by this approach can we be able to understand and appreciate the use of literature in the spheres of education and social activity.* The stimulus for this paper derives from Professor Carter’s valuable insight discussed in his book “Investigating English Discourse”, published in 1997. This paper was delivered as a sub plenary address at the Second International Conference of the Armenian Association for the Study of English (AASE), held at the Yerevan State University, Yerevan on 16 -19, October 2007.